Biocatalytic Resolution of Enantiomeric Mixtures of 1-Aminoethanephosphonic Acid - Paweł Kafarski; Ewa Żymańczyk-Duda; Magdalena Klimek-Ochab; Małgorzata Brzezińska-Rodak (Molecules, 2011)
Several fungal strains, namely Bauveria bassiana, Cuninghamella echinulata, Aspergillus fumigatus, Penicillium crustosum and Cladosporium herbarum, were used as biocatalysts to resolve racemic mixtures of 1-aminoethanephosphonic acid using L/D amino acid oxidase activity. The course of reaction was analyzed by 31P-NMR in the presence of cyclodextrin used as chiral discriminating agent. The best result (42% e.e of R-isomer) was obtained with a strain of Cuninghamella echinulata.